PENGEMBANGAN KAMPUNG KREASI EKOWISATA BERBASIS PEMBERDAYAAN MASYARAKAT (STUDI PADA KAMPUNG KREASI KELURAHAN SIDOKUMPUL, KABUPATEN GRESIK) - Muhammad Firdaus Alamsyah; Tjitjik Rahaju (Publika, 2022)
Kampung is an environmental unity inhabited by family units that have the characteristics of strong family ties. As the times progressed, the village began to change face. One of them is related to the innovation of the village order, which is being developed related to tourist villages. One of them is related to the innovation of the village order, which is being developed related to tourist villages. In Kampung Jagal, Sidokumpul Village, Gresik Regency, also developed a tourist village that utilizes waste management based on community empowerment. In this article aims to get an overview of the stages of development of ecotourism creation village based on community empowerment in Kampung Jagal. The method used is a qualitative description using the theory of the Delivery Team (Mardikanto Totok, 2013: 125-127) related to the stages of community empowerment. Which consists of location selection, community empowerment socialization, community empowerment process, and community self-sedition. The results showed that the development of creation villages in Kampung Jagal has gone through several stages in accordance with the theory of the Delivery Team (Mardikanto Totok, 2013: 125-127) and has a positive impact related to changes in behavior and community mindset related to the environment and waste utilization. Keywords: Creation Village, Tourism Village, Community Empowerment.